Interactive space: Searching for a dual physical - Virtual world - Rahaman, H. (2013)
2009 TAIWAN CAADRIA: Between Man and Machine - Integration, Intuition, Intelligence - Proceedings of the 14th Conference on Computer-Aided Architectural Design Research in Asia